Variational inference of differential equations of vibrations of piezoceramic shell with meridional polarization - Lastivka, I.O. (Carpathian Mathematical Publications, 2014)
A construction of one embodiment of refined theory of piezoceramic shell with the meridional polarization was proposed, a system of differential equations of membrane vibrations and the boundary conditions using the variational Reissner principle was obtained.